Malignant Ventricular Arrhythmic Storm Triggered by Short-coupled Premature Ventricular Contractions Arising from the Anterolateral Papillary Muscle. (2016) - Kabunga, Peter; Medi, Caroline; Yeates, Laura; Sy, Raymond W
No abstract available